THE EFFECT OF USING â€œTHE POWER OF TWOâ€ STRATEGY ON THE ABILIT OF THE SEVENTH GRADE STUDENTS OF SMP BABUSSALAM PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Toyibah, Zuriat; Supriusman, Supriusman; Safriyanti, Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to find out the significant effect of using the power of two Strategy on the ability of the seventh grade students of SMP Babussalam Pekanbaru in comprehending descriptive texts. The selected sample was VII.4 class. The sample was selected by using random sampling technique. This research used pre-experimental research design for one group pre-test post-test and the data were collected by using on written test on descriptive texts. The instrument used in this research was multiple choice test consisted of four options â€œ(A/B/C/D)â€. The result of the study showed that the mean score of the pre -test was 63.04 while the result of the post-test was 79.16. Therefore, it can be concluded that there is a significant effect of using the power two strategy on the ability of the seventh grade students of SMP Babussalam Pekanbaru in comprehending descriptive texts. It can be stated that the alternative hypothesis (Ha) is accepted. In conclusion, teachers are suggested to use the Power of Two as one of the alternative strategies in improving studentsâ€™ comprehension of descriptive texts.Key Words: Effect, The Power of Two strategy, Comprehending, Descriptive Text